An assessment on S&T careers leading to technology creation - Esquivel, Susana F.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, 2010)
The Department of Science and Technology through the Science Education Institute (DOST-SEI) which implements various undergraduate scholarship programs in the country is continuing its efforts to attain the status of a Newly Industrializing Country (NIC). Since 1958 the scholarship programs produced a lot of scholar-graduates who are now in their respective fields in the industry. However, despite its aim to ensure a steady, adequate supply of qualified S&T human resources which can steer the country towards national progress, there are scholars who work abroad to find greener pasture. There are also those who graduated but to date did not report about their employment status. Thus, the number of human resources decreases and its accumulation from the time the scholarship programs started is a big deduction on what they can contribute to the country. The outcome of the study revealed that the DOST-SEI has a great impact in providing the RA7687 Scholarship Program to deserving and talented students with high aptitude in science and mathematics. The basic criteria of eligibility, i.e. the student must belong to the upper 5 percent of the graduating class is truly an effective strategy of the lawmakers to get the cream dela cream among students who can steer the country towards national progress. The implementation scheme of the program is already established. However, the government has no specific strategy yet on how these scholars will be deployed accordingly. The DOST-SEI has no strong linkage with the industries that will lead these scholars to develop their undergraduate training. The quality of education that SUCs provided will not be meaningful if these scholars will not be placed according to their fields of specialization. Advanced countries are spending a lot not only in producing human resources but more importantly in R&D which is the key to becoming independent scientifically and technologically. This is another major area that the government should work on by providing a big portion of the national budget in R&D.
The study revealed that as of now, the goal of the DOST-SEI stays in developing human resources in the various fields of basic and applied sciences. As of now, there is no specific tracking system that maybe used as basis to formulate policies that will boost the country to economic development and catch-up. Since 2008, the DOST-SEI started to implement the Accelerated S&T Human Resources Development Program (ASTHRDP) which is a good start to producing not only BS but MS and PhD scholars as well. The government of advanced countries' primary expenditures are spent on human resource development and R&D. The Philippine government has started in developing its human capital. It should also focus its primary spending in R&D. Science and technology parks encourage companies to expand their tax base and employment opportunities to citizens. This is one of the strategies that the government may do to lessen the problem on brain drain in our country. We should be the one to benefit from our pool of S&T experts. Thus, the government should really protect these talented minds by providing technical assistance and programs that will encourage them not to leave the country. The initial and primary move should come from the government. It should strongly address the triple helix of innovative collaboration of the government, academe and private sector that would turn the country to a virtuous circle of S&T development. Policies should be formulated on this regard so we can start anew to bring back the innovative leadership we had before.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Technological innovations; S&T careers